2010
DOI: 10.1080/13691050903471441
|View full text |Cite
|
Sign up to set email alerts
|

‘I just need to be flashy on campus’: female students and transactional sex at a university in Zimbabwe

Abstract: This paper challenges two common perceptions regarding transactional sex relationships particularly in Africa: that they are primarily resorted to as survival strategies by economically disadvantaged young women and that sex and money are always exchanged within these relationships. Instead, I show how, in reality, young women and the men they date may use these relationships primarily to compete for social status in their peer groups as well as to fashion themselves as high-status, successful modern subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 24 publications
5
91
0
Order By: Relevance
“…At the same time, however, and reinforcing the findings of Masvawure (2010a), there are clear signs in participants' narratives that transactional sexual encounters on campus are not simply about money but also involve a range of material and emotional transactions that can confer benefits on both men and women. Women are not necessarily passive victims in these exchanges, they may actively and strategically engage in such relationships as has been argued by Gukurume (2011) in his study on a higher education campus in Zimbabwe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, however, and reinforcing the findings of Masvawure (2010a), there are clear signs in participants' narratives that transactional sexual encounters on campus are not simply about money but also involve a range of material and emotional transactions that can confer benefits on both men and women. Women are not necessarily passive victims in these exchanges, they may actively and strategically engage in such relationships as has been argued by Gukurume (2011) in his study on a higher education campus in Zimbabwe.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies at university campuses have further illustrated the salience of transactional relationships for the purposes of status and material gain (including access to clothes, cell phones, driving in smart cars, wearing fashionable clothes and so on). These have also foregrounded the resilience of heteronormative gender inequalities in contemporary relationships (Clowes et al 2009;Gukurume 2011;Masvawure 2010aMasvawure , 2010bShefer and Foster 2009). In the light of this work, and since there is concern about the HIV status of young people at universities and practices of coercive sex and gender-based violence, it is important to gain further insight into the particular understandings and reported dynamics of transactional sexual relationships at South African universities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, male respondents generally felt obliged on moral grounds to pay womenbecause they perceived them as being economically disadvantaged. The ambiguities surrounding transactional sex described by respondents in many ways mirror practices observed in sub-Saharan Africa (Masvawure 2010). The relevance that must be drawn here is that future HIV-prevention messaging must account for the possibility that people may not recognise themselves within the 'sex worker/client' discourse and, as a result, may not receive HIV-prevention messages that deploy such terms.…”
Section: Male Respondentsmentioning
confidence: 92%
“…Transactional sex that is not sex work in the traditional sense, nor only an outcome of poverty, but is also fuelled by consumerist pressures to acquire goods and social status, as well as linked with culturally-based notions of gender, love and exchange (see Bhana & Pattman 2011;Hunter 2002Hunter , 2010, has also been shown to be common. Studies have indicated that transactional sexual relationships, especially when they involve a number of power dynamics including age and access to resources, play a significant role in unsafe, unequal and coercive sexual practices, and as a result are receiving increased attention in Africa (Clowes, Shefer, Fouten, Vergnani & Jacobs 2009;Dunkle, Jewkes, Brown, Gray, McIntyre & Harlow 2004;Dunkle, Jewkes, Nduna, Jama, Levin, Sikweyiya, et al 2007;Hallman 2004;Kaufman & Stavros 2004;Leclerc-Madlala 2003;Maganja, Maman, Groves & Mbwambo 2007;Masvawure 2010;Ulin 1992).…”
Section: Introductionmentioning
confidence: 99%